The spatial impact of employment centres on housing markets. Issue 4 (2nd October 2017) - Szumilo, Nikodem; Laszkiewicz, Edyta; Fuerst, Franz
ABSTRACT: The spatial impact of employment centres on housing markets. Spatial Economic Analysis . Local economic growth tends to affect neighbourhood house prices unevenly. It has been observed that prime locations experience price hikes far in excess of the surrounding local area. Yet, this phenomenon is not well captured by existing economic models. This research provides a model of spatial and temporal interactions between housing and employment markets. The results show that rapid growth of employment centres increases house prices in neighbouring locations even after adjusting for fundamentals. It is concluded that spatial clustering of companies creates an option value for existing and potential employees that goes beyond ease of access for commuting purposes.